Effect of a Vulsellum Compared With a Single-Tooth Tenaculum on Pain Perception During Intrauterine Device Insertion [223]. (May 2015) - Doty, Nora; MacIsaac, Laura
Abstract : INTRODUCTION: Intrauterine devices (IUDs) are used by only 3.5% of reproductive-aged women in the United States. One barrier to IUD uptake is fear of pain during insertion, particularly among nulliparous women. Many interventions to reduce pain during IUD insertion have proven unsuccessful. Comparisons of different tenacula have not been previously reported. METHODS: This was a single-blind, randomized control trial of 80 women randomized to the use of a vulsellum or a single-tooth tenaculum during IUD insertion. The primary outcome was reported pain on a 100-mm visual analog scale at the time of vulsellum placement. Secondary outcomes included pain at other intervals during IUD insertion and bleeding from the tenaculum site. Pain scores were analyzed with a Mann-Whitney test because they were not normally distributed. RESULTS: Pain scores at the time of single-tooth tenaculum (33.3 mm) and vulsellum (35.0 mm) placement were the same in both groups ( P =.58). There was no statistically significant difference in the number of maneuvers required to control bleeding at the tenaculum site between the two groups; however, it took longer to control bleeding in the single-tooth tenaculum compared with the vulsellum group (1.1 compared with 0.4 minutes, P =.001). Preprocedure anxiety was significantly correlated with more pain during IUD insertion. CONCLUSION AND IMPLICATIONS: This is the first randomized trial comparing tenacula. There was no difference in reported pain, but the vulsellum may be associated with less bleeding than a single-tooth tenaculum. Women with higher preprocedure anxiety experienced more pain during IUD insertion. Future research could investigate an anxiolytic's effect on pain during IUD insertion.